The contribution of seedbank to the green roof plant community dynamics analogous to semi-natural grasslands - Rivière, Lucie; Sellier, Alizé; Dutoit, Thierry; Vidaller, Christel; Buisson, Elise; Mahy, Grégory (Frontiers in Ecology and Evolution, 2023)
Extensive green roofs have been shown to support native biodiversity and plant communities that are analogous to natural or semi-natural habitats such as grasslands. However, little is known about the role of soil seedbanks in the dynamic of extensive green roof plant communities. The purpose of this study was to analyze the seedbank that developed after four years of an extensive green roof analogue to dry grassland plant community, seeded with 29 species. We aimed to understand the contribution of seedbank to the resilience of vegetation to harsh conditions of the roof and to colonization by surrounding spontaneous species. We monitored the plant species cover in 36 plots during four years in June (between 2018 and 2021), and sampled the seedbank in February 2021. Our results showed that the soil seedbank was dominated by transient spontaneous ruderals species, while the standing vegetation was still dominated by seeded grassland species. We found that seeded grassland species had poor seedbank stock, similar to their natural environments. The similarity index between the standing vegetation and the seedbank increased over time, and we measured a significant correlation between dominant species cover and their seedbank density. Spontaneous species cover was not correlated to the proportion of soil not colonized by seeded species cover, indicating that gaps in vegetation did not influence the development of spontaneous species. Our findings highlight the importance of seedbank in the dynamic of green roof vegetation and demonstrate that analogous habitat species exhibit similar behavior as in their natural environments.